Translanguaging in Arabic Language Learning: Patterns, Impacts, and Pedagogical Implications for Students - Moh. Subthi Buchori; M. Ainur Roziqi; Moh. Anwar; Sugeng Ali Mansur (UIN Maulana Malik Ibrahim Malang, 2025)
The phenomenon of translanguaging is increasingly prevalent in language classrooms, including Arabic language learning in higher education. Students not only use Arabic but also blend it with Indonesian or regional languages to clarify meaning and enhance comprehension. This study aims to identify the patterns of translanguaging employed by students, analyze its impact on the learning process, and explore the pedagogical implications of this phenomenon.Using a descriptive quantitative approach through questionnaires distributed to students in the Arabic Language Development Program at several public and private universities in Malang, data were analyzed using descriptive statistics (percentages and means) alongside simple thematic analysis of open-ended questions to complement quantitative findings. The results indicate that translanguaging not only helps students understand material more effectively but also increases participation and self-confidence. However, this practice may also lead to overreliance on the first language.Pedagogically, translanguaging holds significant implications. It can be positioned as a teaching strategy in the early stages of language learning. Instructors need to develop their ability to use translanguaging strategically and avoid excessive reliance. Furthermore, accommodating translanguaging in the design of Arabic language curricula in Indonesia is essential. Thus, it is crucial for educators to manage translanguaging strategically in Arabic language instruction.